Alih Wujud Ide Lingual Ke Visual dalam Penciptaan Tugas Akhir S-1 Kriya Isi Yogyakarta - Angel, Birgita; Purwandari, Retno (Institut Seni Indonesia Yogyakarta, 2024)
The creation of final project works of ISI Yogyakarta Craft students inrecent years has experienced rapid development related to the source of ideasbehind it. What is commonly created is a craft work with a source of ideas in theform of concrete forms, such as living things or concrete objects around. This isof course not too constrained in the method of creation because of thetransformation of concrete ideas into the design of works in the form of visualforms, of course, there are many stages of creation methods and visualizationtheories available in the field of crafts. However, this is not the case, if the sourceof the idea of creation is a lingual form. The science of interpreting lingual ideasto be transformed into visual forms needs to be studied further because no crafttheory can accommodate this process. What is happening now is that, thecreation of Kriya's final project work has begun to penetrate wider sources ofcreation, one of which is the source of ideas in the form of literary works and songlyrics. This qualitative research tries to unravel the creation of the final project ofcraft students that is sourced from lingual ideas, to find out how the stages of itscreation, the process of transforming lingual ideas into their visual form, and findout what theory is used whether it has functioned theoretically or not. If thesequestions have been answered, it is hoped that this research will be able to designa method of creation, including stages, techniques, and theories used for thetransfer of lingual ideas to visual forms in the creation of craftworks. The Level ofTechnology Readiness (TKT) of this research is expected to be in the level 3category, namely by proving the concept of functions and/or importantcharacteristics analytically and experimentally.ABSTRAKPenciptaan karya tugas akhir mahasiswa Kriya ISI Yogyakarta beberapa tahun terakhir mengalami perkembangan pesat berkaitan dengan sumber ide yang melatarbelakanginya. Yang sudah biasa diciptakan adalah karya kriya dengan sumber ide berupa wujud konkret, seperti makhluk hidup ataupun benda konkret di sekitar. Hal tersebut tentu saja tidak terlalu terkendala dalam metode penciptaannya karena mengalihwujudkan ide konkret ke dalam rancangan karya yang berupa wujud visual tentunya sudah banyak tahapan metode penciptaan serta teori visualisasi yang tersedia dalam bidang kriya. Namun tidak demikian, apabila sumber ide penciptaan berupa wujud lingual. Keilmuan memaknai ide lingual untuk dialihwujudkan ke bentuk visual perlu ditelaah lebih lanjut karena belum ada teori kriya yang bisa mewadahi proses tersebut. Yang terjadi saat ini, penciptaan karya tugas akhir kriya mulai merambah ke sumber penciptaan lebih luas, salah satunya sumber ide berupa karya sastra dan karya lirik lagu. Penelitian kualitatif ini mencoba mengurai penciptaan tugas akhir mahasiswa kriya yang bersumber ide lingual, untuk mengetahui bagaimana tahapan penciptaannya, proses alih wujud ide lingual ke bentuk visualnya, serta mengetahui teori apa yang digunakan apakah sudah berfungsi secara teoretis ataukah belum. Jika pertanyaan-pertanyaan tersebut sudah terjawab, diharapkan penelitan ini mampu merancang metode penciptaan termasuk di dalamnya meliputi tahapan, teknik, dan teori yang digunakan untuk pengalihwujudan ide lingual ke bentuk visual dalam penciptaan karya kriya. Tingkat Kesiapan Teknologi (TKT) penelitian ini diharapkan masuk kategori level 3, yakni dengan melakukan pembuktian konsep fungsi dan atau karakteristik penting secara analitis dan eksperimental.